Enhanced anticancer effect of thymidylate synthase dimer disrupters by promoting intracellular accumulation - Marverti, Gaetano; Moschella, Maria Gaetana; Belardo, Alice; Lamesta, Michele; Mercanile, Giada; Tagliazucchi, Lorenzo; Aiello, Daniele; Venturelli, Alberto; Illuminati, Davide; Guerrini, Remo; Losi, Lorena; Ponterini, Glauco; et al. (Frontiers in Pharmacology, 2024)
Human Thymidylate synthase (hTS) plays a key role in cellular growth, proliferation, DNA synthesis, and repair; thus, gaining attention for targeted therapies in cancer. Its overexpression and altered pharmacokinetics, leading to reduced drug accumulation, are among the most prominent causes of cellular resistance. The latter occurs either through decreased drug influx and/or increased efflux, resulting in reduced drug access to the intracellular targets. In this study, we have evaluated and demonstrated the increased cytotoxic efficacy of novel hTS dimer disrupters (Ddis) in the presence of specific inhibitors of drug efflux protein pumps in ovarian and colon cancer cell lines, suggesting that these compounds are substrates of the cellular drug extruders. A second strategy adopted to increase intracellular accumulation was a drug delivery system. These hold promises in helping the less lipophilic compounds from crossing the cell membrane. The Ddis compounds were delivered through the SAINT-Protein transfection agent. The observed cell-killing effects agreed with the reduction of hTS protein level and cell cycle perturbation. Overall, this preclinical study suggests that the innovative hTS dimer disrupters can achieve a higher efficacy by favoring their intracellular accumulation. This can be obtained by both reducing their outflow and/or increasing cellular uptake.